(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Pragmatics is the study of language use in context. It is concerned with how people use language to communicate their intentions, beliefs, and emotions. Image-bearing stylistic devices are literary devices that create vivid and memorable images in the reader’s mind. These devices can be used to evoke a wide range of associations and emotions, and they can be used to create a variety of effects in fiction.